Phenotypic and Genotypic Characterization of Mycobacterium africanum Isolates from West Africa - Frothingham, Richard (American Society for Microbiology, 1999)
The Mycobacterium tuberculosis complex includes M. tuberculosis, M. bovis, M. africanum, and M. microti. Most clinical isolates are M. tuberculosis or M. bovis. These species can be distinguished by phenotypes and genotypes. However, there is no simple definition of M. africanum, and some authors question the validity of this species. We analyzed 17 human isolates from Sierra Leone, identified as M. africanum by biochemical and growth characteristics. We sequenced polymorphic genes and intergenic regions. We amplified DNA from six loci with variable numbers of tandem repeats (VNTRs) and determined the exact number of repeats at each locus in each strain. All M. africanum isolates had the ancestral CTG Leu at katG codon 463. Drug-resistant M. africanum isolates had katG and rpoB mutations similar to those found in drug-resistant M. bovis and M. tuberculosis. Fourteen Sierra Leone M. africanum isolates (designated group A) had katG codon 203 ACC Thr, also found in M. africanum(T) (the T indicates type strain) from Senegal. Group A isolates clustered with M. africanum(T) by VNTR analysis. Three M. africanum isolates (group B) had katG codon 203 ACT Thr, found in M. tuberculosis(T), and clustered with M. tuberculosis(T) by VNTR analysis. Phenotypic identification of M. africanum yielded a heterogeneous collection of strains. Genotypic analyses identified a cluster (M. africanum group A) which included M. africanum(T) and was distinct from the rest of the M. tuberculosis complex. Future studies of M. africanum should include both phenotypic and genotypic analyses.